The Gap between the Beginning and the End of Algebraic Thinking Transition Period - Permatasari, Dian; Harta, Idris (Universitas Ahmad Dahlan, 2018)
Algebraic thinking is an important element in mathematics thinking and reasoning. All students experience a transition to algebraic thinking. It happens from elementary school grade V until junior high school grade VII. This study aims to describe the differences in algebraic thinking ability from the beginning of transition period, elementary school grade V, until the end of the transition period, junior high school grade VII. This research was a cross-sectional research using mixed method approach. The results showed that students' algebraic thinking ability at the beginning of the transition period and at the end of the transition period was in moderate criteria. The average score in algebraic thinking test at the end of the transition period, junior high school grade VII, was higher than the students in junior high school grade V, but the algebraic thinking ability of students in elementary school grade V did not have much different with the students of junior high school grade VII, that was in the moderate criteria.